Transient changes in L-arginine, asymmetric and symmetric dimethyl arginine in triathletes following Norseman Xtreme Triathlon - Bonnevie-Svendsen, Martin; Nyborg, Christoffer; Bratseth, Vibeke; Melau, Jørgen; Hisdal, Jonny (Frontiers in Physiology, 2024)
Arterial vasodilation is dependent on nitric oxide synthesized from L-arginine by endothelial nitric oxide synthase. Triathletes are reported to display altered serum concentrations of nitric oxide metabolites such as L-arginine, asymmetric dimethyl arginine (ADMA) and symmetric dimethyl arginine (SDMA) shortly after completing long-distance triathlon races. In other populations, similar changes to nitric oxide metabolites are established risk markers of cardiovascular disease. The objective of this study was to assess serum concentrations of metabolites for endothelial nitric oxide synthesis in triathletes at one week following a long-distance triathlon race. In this prospective observational study, we used high-performance liquid chromatography to measure circulating concentrations of L-arginine, ADMA, and SDMA in triathletes. Venous blood samples were collected before, immediately after, day one, and one week following the triathlon race. Serum concentrations and L-arginine/ADMA ratio were determined for each time-point and compared to baseline. L-arginine/ADMA ratio was reduced on day one (147 ± 32 vs. 163 ± 40, p < 0.02). ADMA was reduced immediately after and increased at day one and remained elevated at one week (0.29 ± 0.05 µM, p < 0.001, 0.44 ± 0.08 µM, p < 0.001 and 0.42 ± 0.07 µM, p = 0.04, respectively vs. 0.40 ± 0.05 µM). SDMA was increased at all time-points when compared to baseline (0.48 ± 0.10 µM, p < 0.001, 0.53 ± 0.11 µM, p < 0.001 and 0.42 ± 0.08 µM, p = 0.048 vs. 0.38 ± 0.05 µM). L-arginine was only decreased immediately after (46.0 ± 9.3 µM vs. 64.6 ± 16.1 µM, p < 0.001). Long-distance triathlon racing induces altered levels of metabolites for endothelial nitric oxide production that mostly normalizes within one week following racing. The clinical relevance of these transient changes has yet to be elucidated in the athletic population.